2020
DOI: 10.1080/09168451.2019.1685370
|View full text |Cite
|
Sign up to set email alerts
|

MiR-210-3p attenuates lipid accumulation and inflammation in atherosclerosis by repressing IGF2

Abstract: Previous studies have shown that miR-210-3p is involved in the development and progression of atherosclerosis, but its specific mechanisms are still unclear. This study aims to reveal the mechanism of miR-210-3p and its target genes in macrophage lipid deposition and inflammatory response, and provide new ideas for the treatment of atherosclerosis. We found miR-210-3p increased sharply in the first 12 h induced by higher doses of ox-LDL in THP-1 macrophages and then gradually decreased. MiR-210-3p mimic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Similar to the association of miR-221/222 family with dyslipidemia (LDL-C/HDL-C), this phenomenon was also seen on miR-126-5p [16,17]. In addition, miR-490-3p [18], miR-320b [19], miR-210-3p [20], miR-17-3p [21] and miR-33a-5p [22] were linked to LDL-C metabolism while miR-22-3p [23], miR-31-5p [24], miR-378b [25], and miR-135a-3p [26] were linked to HDL-C metabolism. These findings suggested that the all the 40 DE-exo-miRs may be association with lipid metabolism, especially on LDL-C.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar to the association of miR-221/222 family with dyslipidemia (LDL-C/HDL-C), this phenomenon was also seen on miR-126-5p [16,17]. In addition, miR-490-3p [18], miR-320b [19], miR-210-3p [20], miR-17-3p [21] and miR-33a-5p [22] were linked to LDL-C metabolism while miR-22-3p [23], miR-31-5p [24], miR-378b [25], and miR-135a-3p [26] were linked to HDL-C metabolism. These findings suggested that the all the 40 DE-exo-miRs may be association with lipid metabolism, especially on LDL-C.…”
Section: Discussionsupporting
confidence: 64%
“…Participants with T-allele (TT + CT) of rs1799858 were not only associated with increased risk of higher LDL-C level but also with increased risk of atherosclerosis events, including carotid artery stenosis (CAS) ≥ 50% and new-onset/recurrent acute myocardial infarction (AMI). Synchronously, the data reported in this study indicated that those DE-exo-miRs between the two genotypes (CC vs. TT + CT) of rs1799858 were not only involved in lipid metabolism/dyslipidemia as mentioned above but also played a pivotal role in the occurrence and progression of arteriosclerosis [27,28], such as miR-22-3p, miR-490-3p, miR-210-3p, miR-497-5p, miR-33a-5p, miR-126-5p, miR-451b, miR-320 family (e.g., miR-320b), miR-208 family (e.g., miR-208b-3p), let-7 family (e.g., let-7i-5p, let-7g-5p, let-7a-5p and let-7f-5p) and miR-221/222 family (e.g., miR-222-3p and miR-221-5p), involving in proliferation and migration of VSMCs (e.g., miR-22-3p [29] and miR-490-3p [18]), ECs dysfunction (e.g., miR-22-3p [30], miR-126 [31], miR-221/222 family [13]), plaque angiogenesis (e.g., miR-126 [32]), apoptosis (e.g., miR-210-3p [33], miR-320d [34]) and macrophage lipid deposition (e.g., miR-210-3p [20]). In particular, miR-483-5p [35], miR-31-5p [36], miR-320b [19] and miR-126 [37] were also closely related to the stenosis degree and unstable phenotype of atherosclerotic plaques, suggesting those exo-miRs may be related to the potential risk of acute vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of IGF-associated miRNAs namely miR-30a-3p, miR-155, miR-199a-3p, and miR-486-5p has important roles in different conditions such as preeclampsia, hepatocellular carcinoma, estrogen-mediated autophagy, and congenital heart disease (El Tayebi et al, 2015;Fu et al, 2018;Niu et al, 2018;Fan et al, 2019). Besides, dysregulation of miR-210-3p, miR-491-5p, and miR-615-3p contributes to the pathogenesis of atherosclerosis, colorectal carcinoma, and non-small lung cancer through modulation of IGF2 expression level (Liu j. et al, 2019;Lu et al, 2019;Qiao et al, 2020). Besides, aberrant expressions of miR-204-5p, miR-197, and miR-155-5p participate in the pathogenesis of papillary thyroid carcinoma, colorectal cancer, and non-small lung cancer through affecting expressions of IGFBP5, IGFBP3, and IGFBP1, respectively (Ling et al, 2015;Liu L. et al, 2015;Zheng et al, 2018).…”
Section: Igf-associated Mirnas In Human Disordersmentioning
confidence: 99%
“…MYC can form a complex with kaposin B, which is another KSHV latent protein, to modulate the expression of a wide variety of host microRNAs [ 120 ], some of which, such as miR-210 [ 121 , 122 , 123 , 124 , 125 ], miR-3188 [ 126 ], miR-483-3p [ 127 ], miR-3197 [ 128 ], miR-423-5p [ 129 ], let-7f-5p [ 130 ], miR-372-3p [ 131 ], miR-9-5p [ 132 , 133 ], miR-489-3p [ 134 ], miR-1271-5p [ 135 ], miR-7-5p [ 136 ] miR-942-3p [ 137 ] and miR-153-3p [ 138 , 139 ], have been linked to metabolism in other diseases. In addition, the KSHV latent protein vIRF3 can stimulate the transcriptional activity of MYC by interacting with Skp2, a transcriptional cofactor that stabilizes and upregulates MYC activity [ 140 ].…”
Section: Regulation Of Myc By Dna Tumor Virus Oncoproteinsmentioning
confidence: 99%